Perancangan Sistem Informasi Pengelolaan dan Monitoring Mobil Berbasis Web Menggunakan Pendekatan OOAD - Rio Adi Lukmana; Dandi Fajar Ismail; Gunung Tegar Abadi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to design a web-based information system for vehicle management and monitoring at Bengkel Merdeka Motor, which previously relied on manual recording processes. Manual data management caused several problems, including data loss, inaccurate records, difficulties in monitoring service progress, and delays in report generation. This research applies the Object-Oriented Analysis and Design (OOAD) method supported by Unified Modeling Language (UML) to analyze system requirements and design the proposed system. The research methodology includes requirements analysis, analysis of existing and proposed systems, system design, and user interface design. The proposed system integrates vehicle data management, service offers, work orders (SPK), service progress monitoring, invoice generation, and automatic monthly reporting into a single web-based platform. The results show that the designed system improves data accuracy, operational efficiency, and transparency of service information. In addition, real-time monitoring features support better coordination between administrators and mechanics. The implementation of this system is expected to enhance service quality, reduce administrative errors, and support managerial decision-making at Bengkel Merdeka Motor.